Energy crops for sustainable phytoremediation – Thermal decomposition kinetics. (February 2019) - Trinh, Thuat T.; Werle, Sebastian; Tran, Khanh-Quang; Magdziarz, Aneta; Sobek, Szymon; Pogrzeba, Marta
Abstract: The thermal decomposition kinetics of two energy crops Miscanthus x giganteus and Sida hermaphrodita biomass materials harvested from a phytoremediation study in Polish and Germany have been studied, assuming a three-pseudocomponent model. The kinetic parameters extracted from the study are realistic and within reasonable ranges. The activation energies are within 20 - 103.55 kJ/mol. The reaction orders are within 1.01-1.99. The result shows that the energy crops from the Polish site exhibited higher conversion rates than the samples from Germany. A negative effect of the ash content on the biomass reactivity is observed.